Voice and Video Transmission with Mobile IPv6 - Idris, Fakrulradzi; Hashim, Norlezah (2010)
Mobile IPv6 (MIPv6) is a protocol that is proposed for the future of the mobile Internet access. The aim of MIPv6 is to provide seamless communication services to mobile nodes. The aim of this study is to investigate the effect of real time applications: voice and video transmission on MIPv6 network. In this paper the implementation of MIPv6 and fast handover MIPv6 (FMIPv6) is modeled and simulated using Network Simulator 2 (NS-2) software. The performance is analyzed for three different voice coding schemes and video based on H.263 format for both MIPv6 and FMIPv6.